A Summary of Fatal Accident Due to Flyrock and Lack of Blast Area Security in Surface Mining, 1989 to 1999 - T. R. Rehak; G. L. Mowrey; D. K. Ingram (International Society of Explosives Engineers, 2002)
This paper summarizes flyrock and blast area security fatalities from 1989 to 1999 and examines the causative factors. Coal and nonmetal mining used about 43 billion pounds of explosives and blasting agents between1989 to 1999. A majority of this consumption was used at surface mines. Accident data indicates that flyrock and lack of blast area security were the primary causes of blasting related injuries in surface mining. Fatal injuries due to lack of blast area security were attributed to: failure to clear blast area; failure to follow instructions; inadequate guarding; inadequate blasting shelter; and unsafe location.